Da’wah Visual Channel Telegram Rumaysho - Fajar Tri Akbar (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
A phenomenon that is no longer strange to see today is the use of gadgets by all levels of society, from children to the elderly, all of whom have made gadgets a must-have item and carried everywhere. As an effort to continue to do da’wah productively, da'wah through visual content can be used as a solution to deal with the gadget phenomenon in society and to deal with difficult circumstances and situations during this pandemic. In addition, doing da'wah through visual content is a very significant way to spread Islamic teachings, because the trend of visual content is more favorable and can attract more attention than content that only contains writing. This study aims to determine the content of visual da'wah contained in the posters on the Rumaysho Telegram channel and the techniques used in making these posters. The research method used is descriptive qualitative method, which provides descriptive data from the results of the analysis on the posters of the Rumaysho Telegram channel as many as 10 posters. The data collection technique that the author uses is content analysis. The results of the research that has been done show that the posters on the Rumaysho Telegram channel are made by paying attention to design elements and with various design techniques, then the theme of the message content in each poster is made according to the problems and events that are currently hot in the community. In the future, the Rumaysho Telegram channel is expected to continue to develop its creative ideas and continue to improve the ability of design techniques so that the content presented always feels new, it is also hoped that the Rumaysho Telegram channel can maximize the features available on Telegram so that it can follow the trend of using gadgets by the community. Keywords: visual da'wah; da'wah message; design technique; Telegram channel